1993
DOI: 10.1111/j.1476-4431.1993.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Arrhythmias in Dogs With Splenic Masses

Abstract: The records OJ.Summqy 7" dogs with splenic masses were evaluated retrospectr"ve(yto determine whether ventricular anfythrnias, in the absence OJcltnicaZ@apparent under~ng heati disease, were a common clinical~ndi~. Assoa'ated clinical [aboratov, and patho!ogikjindings were evaluated to searchJor clinical predictors OJventricular arztithmias. Age, breed weigh~sex, co~lan"on abnonna!ihes, electro~te abnormalities, and hemoabdomen were unrelated to the development oJanhythmias (p > 0.05). Anemia was awociated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 7 publications
1
13
0
4
Order By: Relevance
“…It is important the emergency clinician recognize patients with splenic masses and/or haemorrhagic peritoneal effusion may develop additional complications such as significant arrhythmias. Ventricular arrhythmias can be seen in both the perioperative and postoperative period and may be as a result of poor myocardial perfusion secondary to hypoxia, hypovolaemia, anaemia or a neurohormonal response associated splenic manipulation (Keyes & Rush ). Although arrhythmias can occur following splenectomies regardless of underlying splenic disease, it is much more likely associated with dogs who had ruptured splenic masses secondary to neoplasia (Marino et al .…”
Section: Neoplasia‐related Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important the emergency clinician recognize patients with splenic masses and/or haemorrhagic peritoneal effusion may develop additional complications such as significant arrhythmias. Ventricular arrhythmias can be seen in both the perioperative and postoperative period and may be as a result of poor myocardial perfusion secondary to hypoxia, hypovolaemia, anaemia or a neurohormonal response associated splenic manipulation (Keyes & Rush ). Although arrhythmias can occur following splenectomies regardless of underlying splenic disease, it is much more likely associated with dogs who had ruptured splenic masses secondary to neoplasia (Marino et al .…”
Section: Neoplasia‐related Emergenciesmentioning
confidence: 99%
“…). In one study dogs experiencing arrhythmias had a histopathological diagnosis of splenic HSA, haematoma and haemangioma in descending order (Keyes & Rush ). Ventricular arrhythmias resulting in haemodynamic instability may require treatment with an anti‐arrhythmogenic medication.…”
Section: Neoplasia‐related Emergenciesmentioning
confidence: 99%
“…The incidence of ventricular arrhythmias in dogs with splenic disease has been examined in two studies: Keyes and others (1993) and Marino and others (1994). Marino and others (1994) reported that 22 of 50 dogs (44 per cent) with haemangiosarcoma, haematoma or pedicle torsion had rapid ventricular tachycardia (RVT) in the perioperative period – 19 after surgery and three before.…”
Section: Conditions Where Ecg Monitoring Is Advised In the Perioperatmentioning
confidence: 99%
“…Various arrhythmias such as premature ventricular contractions and ventricular tachycardia have been previously reported secondary to heart base tumours (Owen et al 1996;Schuller et al 2007), metastatic cardiac haemangiosarcoma (Aupperle et al 2007) and in a dog with a haemangiosarcoma arising from the right surface of the interventricular septum which caused a right bundle branch block (Chastain et al 1974). Possible causes of the ventricular tachycardia documented in this report include myocardial ischemia, hypoxia and the development of an irritable focus secondary to infiltration of the myocardium by the primary septal mass or myocardial metastases (James and Carrera 1959;Keyes et al 1993), or local or systemic catecholamine release (Keyes et al 1993).…”
mentioning
confidence: 97%